Pseudoalteromonas haloplanktis produces methylamine, a volatile compound active against Burkholderia cepacia complex strains - Sannino, Filomena; Apuzzo, Gennaro Antonio; de Pascale, Donatella; Tedesco, Pietro; Maida, Isabel; Perrin, Elena; Fondi, Marco; Fani, Renato; Marino, Gennaro; PARRILLI, ERMENEGILDA; TUTINO, MARIA LUISA (New Biotechnology, 2017)
The Antarctic marine bacterium Pseudoalteromonas haloplanktis TAC125 has been reported to produce several Volatile Organic Compounds (VOCs), which are able to inhibit the growth of Burkholderia cepacia complex (Bcc) strains, opportunistic pathogens responsible for the infection of immune-compromised patients. However, no specific antibacterial VOCs have been identified to date. The purpose of the present study was to identify specific VOCs that contribute to Bcc inhibition by the Antarctic strain. When grown on defined medium containing D-gluconate and L-glutamate as carbon, nitrogen and energy sources, P. haloplanktis TAC125 is unable to inhibit the growth of Bcc strains. However, single addition of several amino acids to the defined medium restores the P. haloplanktis TAC125 inhibition ability. With the aim of identifying specific volatile compound/s responsible for Bcc inhibition, we set up an apparatus for VOC capture, accumulation, and storage. P. haloplanktis TAC125 was grown in an automatic fermenter which was connected to a cooling system to condense VOCs present in the exhaust air outlet. Upon addition of methionine to the growth medium, the VOC methylamine was produced by P. haloplanktis TAC125. Methylamine was found to inhibit the growth of several Bcc strains in a dose-dependent way. Although it was reported that P. haloplanktis TAC125 produces VOCs endowed with antimicrobial activity, this is the first demonstration that methylamine probably contributes to the anti-Bcc activity of P. haloplanktis TAC125 VOCs.